Rural Roads and Firm Outcomes in India - Bharti Nandwani; Punarjit Roychowdhury; Binay Shankar (Global Labor Organization (GLO), 2025)
This paper examines the impact of a large-scale rural road construction program-the Pradhan Mantri Gram Sadak Yojana (PMGSY)-on the performance of rural manufacturing firms in India. While these firms provide vital non-farm employment in rural areas, their growth is often thought to be constrained by inadequate infrastructure. Leveraging administrative data and the quasi-random rollout of the program, we estimate effects using a two-way fixed effects framework. We find no evidence that improved road connectivity affects turnover, profits, or employment for formal enterprises. In contrast, informal firms experience significant gains in turnover, expenditure, profits, employment, and wage bills. These effects appear to be driven by reductions in infrastructure-related constraints: treated firms report fewer operational problems and less competition from larger firms, particularly in marketing and distribution. Our findings highlight the heterogeneous effects of rural infrastructure expansion and the greater responsiveness of informal enterprises.
Keywords: D22; O12; O18; 330; Firms; India; Infrastructure; Roads; Rural